(untitled) (Research in Agriculture Livestock and Fisheries, 2022)
Reducing income inequality in Africa rests on agricultural total factor productivity (TFP) growth and convergence. Liberalizing agricultural trade has emerged as a force of agricultural TFP growth convergence. Notwithstanding increasing agricultural trade, TFP in Africa is falling while the differences in TFP growth rates remain wide. We provide evidence on the impact of agricultural trade liberalization on agricultural TFP growth convergence. We examine trade by origin, disaggregated into intra-Africa, and rest-of-the-world trade. Also, we recognize the uniqueness of agricultural trade liberalization and analyze the effect of the removal of trade-distorting agriculture support. Using maize and rice data for the period 2005-2016, we apply a Feasible-Generalized- Least-Squares estimation of panel data models derived from Barro and Sala-i-Martin (1990). We find evidence for both absolute and conditional convergence, which is stronger for maize. Moreover, agricultural trade openness speeds up TFP growth convergence for both crops. Convergence speed is higher for intra-Africa trade. Estimations on domestic agriculture support suggest that reduction of support beyond distortion-free levels enhances TFP growth convergence. Our findings call for more agricultural trade liberalization. We appeal that the recently launched Africa Continental Free Trade Area prioritizes intra-Africa agricultural trade liberalization and further elimination of trade-distorting domestic agriculture support. Vol. 9, No. 2, August 2022: 71-88